HP1alpha recruitment to DNA damage by p150CAF-1 promotes homologous recombination repair - Baldeyron, Céline (2011)
Heterochromatin protein 1 (HP1), a major component of constitutive heterochromatin, is recruited to DNA damage sites. However, the mechanism involved in this recruitment and its functional importance during DNA repair remain major unresolved issues. Here, by characterizing HP1α dynamics at laser-induced damage sites in mammalian cells, we show that the de novo accumulation of HP1α occurs within both euchromatin and heterochromatin as a rapid and transient event after DNA damage. This recruitment is strictly dependent on p150CAF-1, the largest subunit of chromatin assembly factor 1 (CAF-1), and its ability to interact with HP1α. We find that HP1α depletion severely compromises the recruitment of the DNA damage response (DDR) proteins 53BP1 and RAD51. Moreover, HP1α depletion leads to defects in homologous recombination-mediated repair and reduces cell survival after DNA damage. Collectively, our data reveal that HP1α recruitment at early stages of the DDR involves p150CAF-1 and is critical for proper DNA damage signaling and repair.